Psychosocial Experiences and Needs of Australian Caregivers of People with Stroke: Prognosis Messages, Caregiver Resilience, and Relationships - El Masry, Y.; Mullan, Barbara; Hackett, M. (Thomas Land Publishers, Inc., 2013)
Background and Objective: Despite stroke being the most common form of cerebrovascular disease, there has been relatively little attention paid to the psychosocial experiences and needs of Australian caregivers of people who have had a stroke. Methods: Twenty Australian informal caregivers and 10 stroke survivors participated in individual semi-structured qualitative interviews covering all aspects of caregiving, including stroke survivors’ views on their caregiver’s experiences. Results: The 5 interrelated topics most discussed were changes in relationships and support services, including being told to expect a poor outcome; caregiver attributes and coping strategies; stroke survivor limitations; external employment and financial stressors; and unexpected positive changes in relationships and priorities. Caring for a stroke survivor involves a complex interaction of these factors that appear to be moderated by the quality of the pre-existing stroke survivor–caregiver relationship and the poststroke coping strategies used. Conclusions: Particular attention should be paid to how prognosis is conveyed and whether appropriate outpatient services are available. Clinicians should also consider discussing appropriate caregiver coping strategies and the quality of the relationship between the stroke survivor and caregiver.